The role of penicillin in modern medicine - Grumach, Anete S; Ferraroni, Natasha R (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Penicillin was the first antibiotic described in the literature in the 1940’s, and it still has a role in the modern medicine. The use of this drug has been amplified since its description, and nowadays, it continues to be the treatment of choice in some diseases. This paper has the objective to describe the importance of penicillin on the actual context, and further, explain the immune mechanisms of adverse reaction to drugs, including penicillin allergy. It is also presented that the anaphylactic reaction is uncommon and it is frequently mistaken diagnosed by doctors and health staff. Such mistake leads to the substitution of this drug, that even described long time ago continues relevant to the treatment of syphilis.